Estimating consumer preferences for different beverages using the BLP approach - Catherine Haeck; Nicholas Lawson; Krystel Poirier (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2022)
The overconsumption of sugar is a significant problem in many jurisdictions, and one possible method to remedy this problem is the taxation of sugarsweetened beverages (SSBs). To be able to implement an optimal tax, it is important to know the preferences and price sensitivity of consumers. This article therefore estimates the price elasticity of demand for different beverages in Quebec, using the Berry, Levinsohn and Pakes (BLP) random parameter logistic demand model, combined with Nielsen data from 2010 to 2016 and the 2016 Canadian Census. The results suggest that the average consumer prefers high-calorie beverages containing fruits and vegetables, and the estimated price elasticities are between -4.40 (energy drinks) and -1.59 (regular soft drinks). As a result, consumers of energy drinks appear to reduce their consumption the most in the face of rising prices, whereas consumers of soft drinks will decrease their consumption the least. However, at a general level, the implementation of a tax on SSBs in Quebec should generate a significant reduction in consumption.
Keywords: I12; I18; D12; H23; 330; sugar-sweetened beverages; price elasticity of demand; BLP; taxation